If It Ain’t Broke…Copyright’s Fixation Requirement and Cultural Citizenship - Mann, Larisa (The Columbia Journal of Law & the Arts, 2011)
Copyright subsists in creative works that are “fixed in any tangible medium of expression,” usually understood as making fixation a prerequisite for protection.1 However, some argue that denying copyright to unfixed works unfairly denies protection to certain classes of artists or works, and that fairness, or concern for those classes of artists or genres, requires that they receive the benefit of copyright ownership for those unfixed works. These arguments generally assume the benefits of copyright protection to the artist, and often by unexamined extension to society. However, copyright ownership has social costs as well as social benefits. This Article examines the possible costs of applying copyright protection to unfixed works, in the context of the specific artists, traditions, genres and practices that rely mainly on unfixed works. It argues for a deeper, more empirically grounded understanding of the creative process and a broader definition of values that arise from culture making, and thus a broader understanding of the public policy implications in copyright law.